Economic impacts of rainfall and temperature towards rubber production / Muhammad Amirul Syafiq Suhaidi - Syafiq Suhaidi, Muhammad Amirul (Faculty of Plantation and Agrotechnology, 2016)
Nowadays, the rubber cultivation industry or the rubber upstream sector has become a major raw material supplier in our country. Peninsular Malaysia has been the world's most important rubber cultivation area (Collins et al., 1991). In the year of 2005, Indonesia, Thailand and Malaysia have produced 33 %, 23 % and 13 % respectively of the world's natural rubber. Lately, the rubber plantation area has been decreasing in Malaysia. The reduction of the production of the rubber is known to be impacted by the temperature and rainfall. A rainfall increasing is prejudicial for rubber plantations which suffer due to loss of tapping days and crop washouts and with excessive temperature, the latex can dry quickly at tapping path without drop at cup and may cause reducing in rubber production. Thus, this study was done to determine the relationship between rainfall and temperature with rubber yield and the effect of rainfall and temperature changes towards rubber yield and cost. The data analysis that was used to analyse the data are descriptive analysis, correlation, and regression method. At the end of this study, the results show that there are significant economic impacts of rainfall and temperature towards rubber production.